CLINICAL AND LABORATORY DIAGNOSTICS OF HEMOLYTIC ANEMIA - Turakulov Javlon Sodik ugli; Tursunov Feruz Uktamovich; Jumanova Parizod Dilmurod kizi (Web of Journals Publishing, 2025)
The relevance of laboratory diagnosis of hemolytic anemia lies in the high level of their occurrence, as well as the complexity of the clinical picture, which requires accurate and timely detection. Hemolytic anemia is a group of diseases characterized by accelerated destruction of red blood cells, which leads to a lack of oxygen in organs and tissues, and also causes a variety of complications.
Keywords: Hemolytic anemia, hereditary and acquired, laboratory research methods, treatment.